2012
DOI: 10.1002/ece3.341
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiking with forests: population genetics of the epiphytic lichenLobaria pulmonariain primeval and managed forests in southeasternEurope

Abstract: Availability of suitable trees is a primary determinant of range contractions and expansions of epiphytic species. However, switches between carrier tree species may blur co-phylogeographic patterns. We identified glacial refugia in southeastern Europe for the tree-colonizing lichen Lobaria pulmonaria, studied the importance of primeval forest reserves for the conservation of genetically diverse populations and analyzed differences in spatial genetic structure between primeval and managed forests with fungus-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 59 publications
4
60
0
Order By: Relevance
“…however, in some cases, a single lichen thallus of the species was found at a location or the thalli were badly developed and damaged. There is no data on genetic diversity, except for two locations of L. pulmonaria, which were included in the study of Scheidegger et al (2012). This study found that the Slovenian populations from Rajhenavski Rog and Notranjski Snežnik are admixed i.e.…”
Section: Discussionmentioning
confidence: 92%
“…however, in some cases, a single lichen thallus of the species was found at a location or the thalli were badly developed and damaged. There is no data on genetic diversity, except for two locations of L. pulmonaria, which were included in the study of Scheidegger et al (2012). This study found that the Slovenian populations from Rajhenavski Rog and Notranjski Snežnik are admixed i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the members of the cited genepool showed broader geographic distribution patterns, amongst the individuals from the whole area tested (27). Our newly cited localities from the southwestern part of the country: in West Frontier Mts, in Mt Belasitsa -see here and (16), in Mt Slavyanka and in Mts Rhodopi might be of future interest as being situated in closer directions from the locations of the individuals of the lung lichen, genetically tested from Greece and Montenegro (27), which could represent a reservoir of the other genotype.…”
Section: Discussionmentioning
confidence: 93%
“…There is a gap of nearly 30 years before its reappearance, when (22) and (14) (27). The authors compared several, precisely chosen ones in Austria, Bosnia and Herzegovina, Montenegro, Bulgaria and Greece by eight fungus-specific genetic markers.…”
Section: Discussionmentioning
confidence: 99%
“…The species is considered extremely sensitive to anthropogenic impact and is used as an indicator of ecological continuity of habitats (Rose, 1992). Over the past 60 years, the world population of L. pulmonaria has declined considerably and at present time it is endangered in many countries of Western Europe (Gauslaa, 1995;Zoller et al, 1999;Gu et al, 2001;Jüriado & Liira, 2009;Mikryukov et al, 2010;Scheidegger et al, 2012). In Russia this lichen is listed in the Red Data Book of the Russian Federation (2008) as well as in many regional Red Data Books, including the Republic of Karelia (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining the effect of time since last disturbance on L. pulmonaria, often reported the species status within two categories-disturbed (managed) forests and old-growth forests, without a clear continuum applicable to forest loss and the initial conditions of forest regeneration (Gu et al, 2001;Scheidegger et al, 2012). However, some researchers have dealt with the longerterm dynamics of L. pulmonaria populations at the level of large spatial units (landscapes) (Snäll et al, 2005).…”
Section: Introductionmentioning
confidence: 99%